2015
DOI: 10.1177/1468018115599818
|View full text |Cite
|
Sign up to set email alerts
|

UNASUR Health: A quiet revolution in health diplomacy in South America

Abstract: Since the creation of Union of South American Nations (UNASUR), health policies became a strategic factor in South America to collectively balance the legacy of neoliberal policies in the region. The aim of this article is first to describe the social, political, and economic processes that explain the emergence of UNASUR and its focus on social policy through healthcare. We then analyze how by virtue of UNASUR’s Health Council, healthcare became the spearhead of cooperation giving way to novel forms of diplom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 25 publications
0
49
0
4
Order By: Relevance
“…Key players include Cuba 104 , and under certain instances Brazil, China, South Africa, and Venezuela 90,105,106 . Various regional blocs also engage in SJSSC, such as ALBA, articulating Third World alliances linked with global civil society 107 , and the Union of South American Nations (UNASUR), which also seeks "de-neoliberalization" via health diplomacy 108 , but not IBSA, which has followed a top-down and mild approach 109 .…”
Section: Cad Saúde Pública 2017; 33 Sup 2:e00194616mentioning
confidence: 99%
“…Key players include Cuba 104 , and under certain instances Brazil, China, South Africa, and Venezuela 90,105,106 . Various regional blocs also engage in SJSSC, such as ALBA, articulating Third World alliances linked with global civil society 107 , and the Union of South American Nations (UNASUR), which also seeks "de-neoliberalization" via health diplomacy 108 , but not IBSA, which has followed a top-down and mild approach 109 .…”
Section: Cad Saúde Pública 2017; 33 Sup 2:e00194616mentioning
confidence: 99%
“…These processes suggest that global health diplomacy and global health governance were attracting increasing foreign policy attention from governments, and were a growing concern for civil society actors and multilateral institutions [Labonté and Gagnon, 2010] Academic researchers of regional cooperation in South America have observed that the health sector is one of the main examples of Brazil's commitment to the region. Brazil played a central role in the creation and development of the CSS where health ministers of UNASUR members meet to find common ground on promoting health policies and programmes [Herrero and Tussie, 2015;Pinheiro and Gaio, 2016]. Leticia Pineiro and Gabrieli Gaio [2016] suggest that Brazil takes part in this council mainly through the Fiocruz Foundation.…”
Section: Health Cooperationmentioning
confidence: 99%
“…Leticia Pineiro and Gabrieli Gaio [2016] suggest that Brazil takes part in this council mainly through the Fiocruz Foundation. Maria Belen Herrero and Diana Tussie [2015] write that Brazil's contributions to the formation of Instituto Sudamericano de Gobierno en Salud in Spanish (South American Institute of Governance in Health, or ISAGS) under UNASUR included hosting the organization in Rio de Janeiro and providing a start-up grant, and has allowed continued technical work beyond the intermittent meetings of the CSS and its technical groups [Herrero and Tussie, 2015]. The main objectives of ISAGS are to:…”
Section: Health Cooperationmentioning
confidence: 99%
See 2 more Smart Citations